Aerosolized Particle Reduction: A Novel Cadaveric Model and a Negative Airway Pressure Respirator (NAPR) System to Protect Health Care Workers From COVID-19. (July 2020) - Khoury, Tawfiq; Lavergne, Pascal; Chitguppi, Chandala; Rabinowitz, Mindy; Nyquist, Gurston; Rosen, Marc; Evans, James
Objectives: This study aimed to identify escape of small-particle aerosols from a variety of masks using simulated breathing conditions. This study also aimed to evaluate the efficacy of a negative-pressure environment around the face in preventing the escape of small aerosolized particles. Study Design: This study is an evaluation study with specific methodology described below. Setting: This study was performed in our institution's fresh tissue laboratory. Subjects and Methods: A fixed cadaver head was placed in a controlled environment with a black background, and small-particle aerosols were created using joss incense sticks (mass-median aerosol diameter of 0.28 µ). Smoke was passed through the cadaver head, and images were taken with a high-resolution camera in a standardized manner. Digital image processing was used to calculate relative amounts of small-particle escape from a variety of masks, including a standard surgical mask, a modified Ambu mask, and our negative airway pressure respirator (NAPR). Results: Significant amounts of aerosolized particles escaped during the trials with no mask, a standard surgical mask, and the NAPR without suction. When suction was applied to the NAPR, creating a negative-pressure system, no particle escape was noted. Conclusion: We present a new and effective method for the study of small-particle aerosols as a step toward better understanding the spread of these particles and the transmission of coronavirus disease 2019. We also present the concept of an NAPR to better protect health care workers from aerosols generated from the upper and lower airways.